2019
DOI: 10.5664/jcsm.7926
|View full text |Cite
|
Sign up to set email alerts
|

CPAP and Health-Related Quality of Life in Adults With Coronary Artery Disease and Nonsleepy Obstructive Sleep Apnea in the RICCADSA Trial

Abstract: Study Objectives: To determine the effect of continuous positive airway pressure (CPAP) treatment on health-related quality of life (HRQoL) in adults with coronary artery disease (CAD) and nonsleepy obstructive sleep apnea (OSA). Methods: This was a secondary outcome analysis of the RICCADSA trial, conducted in Sweden between 2005 and 2013. Adults with CAD, nonsleepy OSA (apnea-hypopnea index [AHI] ≥ 15 events/h; Epworth Sleepiness Scale [ESS] score < 10) and complete Short-Form (SF)-36 questionnaires at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…9,10 Only 47.2% of participants in the Wallström et al study had nightly use of at least 5 hours with an overall sample mean nightly use of 4.5 ± 2.3 h/night on all nights. 3 Use greater than 4 hours did not alter the findings of this analysis, although CPAP use was weakly related to improvement in Mental Component Summary score, but negatively correlated to the Physical Component Summary score. Of course, it is acknowledged that low nightly use often occurring in clinical trials reflects what is typically seen in clinical practice and has spurred the identification of interventions to promote higher use.…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…9,10 Only 47.2% of participants in the Wallström et al study had nightly use of at least 5 hours with an overall sample mean nightly use of 4.5 ± 2.3 h/night on all nights. 3 Use greater than 4 hours did not alter the findings of this analysis, although CPAP use was weakly related to improvement in Mental Component Summary score, but negatively correlated to the Physical Component Summary score. Of course, it is acknowledged that low nightly use often occurring in clinical trials reflects what is typically seen in clinical practice and has spurred the identification of interventions to promote higher use.…”
mentioning
confidence: 55%
“…Using the SF36 to measure quality of life, Wallström and coworkers compared participants with OSA, an Epworth Sleepiness Scale score < 10, and had undergone treatment for coronary artery disease who received CPAP therapy against those with the same characteristics, but had not received CPAP. 3 Although half of the SF36 within group subscale scores improved with CPAP, there were no statistically significant differences between groups.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Several studies have shown that positive pressure ventilation effectively controls CSA/CSR, with remarkable improvements on several pulmonary endpoints, but there is uncertainty as to whether treatment of CSA/CSR in heart failure is beneficial in terms of quality of life, cardiac function, and cardiovascular outcomes. [1][2][3][4][5][6][7][8] Continuous positive airway pressure (CPAP) provides constant positive pressure. By contrast, adaptive servoventilation (ASV) provides dynamic adjustment (breath by breath) of the pressure support with a backup rate to normalize breathing patterns relative to a predetermined target (different algorithms in use).…”
mentioning
confidence: 99%